Skin Ulcers and Mortality Among Adolescents and Young Adults With Spina Bifida in South Carolina During 2000-2010. (March 2016) - Cai, Bo; McDermott, Suzanne; Wang, Yinding; Royer, Julie A.; Mann, Joshua R.; Hardin, James W.; Ozturk, Orgul; Ouyang, Lijing
The authors investigated 48 deaths (7% death rate) among 690 adolescents and young adults with spina bifida in South Carolina during 2000-2010. The authors used Medicaid and other administrative data and a retrospective cohort design that included people with spina bifida identified using ICD-9 codes. Cox regression models with time-dependent and time-invariant covariates, and Kaplan–Meier survival curves were constructed. The authors found that 21.4% of the study group had a skin ulcer during the study period and individuals with skin ulcers had significantly higher mortality than those without ulcers ( P < .0001). People who had their first skin ulcer during adolescence had higher mortality than those who had the first skin ulcer during young adulthood ( P = .0002; hazard ratio = 10.70, 95% confidence interval for hazard ratio: 3.01, 38.00) and those without skin ulcers, controlling for other covariates. This study showed that age at which individuals first had a skin ulcer was associated with mortality.